Improving Short Story Writing Skills Through the Medium of Song Text with Guided Practice Method - Marganingsih, Marti; Bamiro, Nurudeen Babatunde (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2022)
Penelitian ini bertujuan untuk menemukan media yang tepat sebagai sarana peningkatan keterampilan menulis cerpen para siswa SMAN 2 Maja. Penelitian ini menggunakan metode penelitian tindakan kelas, yaitu menggabungkan suatu tindakan sesungguhnya dengan langkah-langkah penelitian di kelas. Instrumen yang digunakan untuk mengumpulkan data dalam penelitian ini tes dan nontes. Tes digunakan peneliti untuk mengetahui kemampuan peserta didik dalam menulis cerpen, sedangkan bentuk nontes dalam penelitian ini berupa lembar observasi, lembar wawancara, dan lembar jurnal peserta didik yang digunakan untuk mengungkapkan perubahan tingkah laku siswa. Upaya peningkatan keterampilan menulis cerpen siswa kelas XI IPA SMAN 2 Maja berdasar teks lagu dengan metode latihan terbimbing menunjukkan hasil baik. Hasil ini dapat dilihat dari pengamatan penulis terhadap siswa pada tahap I dan tahap II. Pada tahap I tergambar jelas hasil pengamatan unsur-unsur intrinsik siswa dalam menulis cerpen berdasar teks lagu. Sedangkan pada tahap II tergambar jelas hasil pengamatan sikap siswa dalam menulis cerpen berdasar teks lagu. This study aims to find the right media as a means of improvement of short story writing skills of SMAN 2 Maja students. This study uses a classroom action research method, which combines an actual action with research steps in the classroom. The instrument used to collect data in this study was a test and a non-test. The test was used by researchers to determine the ability of students to write short stories, while the non-test forms in this study were in the form of observation sheets, interview sheets, and student journal sheets which were used to reveal changes in student behavior. Efforts to improve the short story writing skills of class XI IPA SMAN 2 Maja students based on song texts with the guided practice method showed good results. These results can be seen from the author's observations of students in stage I and stage II. The results of the first phase of the research include the intrinsic elements of short stories compiled by class XI IPA SMAN 2 Maja students based on the text of the song, namely the theme and message, plot/ plot, background/ setting, characters and characterizations, point of view, language style, cohesiveness.In stage I, it is clear that the results of observing students' intrinsic elements in writing short stories based on song texts are clearly illustrated. While in stage II, it is clear that the results of observing students' attitudes in writing short stories based on song texts are clearly illustrated. The results showed that the students felt happy and understood when writing short stories based on song texts so that the writings were interesting.